Stability Analysis of Shallow Goaf Based on Field Monitoring and Numerical Simulation: A Case Study at an Open-Pit Iron Mine, China - Hanwen Jia; Hanwen Jia; Baoxu Yan; Kai Guan; Honglei Liu; Qinzheng Wu; Yantian Yin; Huanxin Liu (Frontiers in Earth Science, 2022)
Evaluation of the stability of a shallow goaf in an open-pit iron mine is important for successful mining. Based on the idea of “rock disaster analysis and prediction combining field monitoring and numerical simulation,” a modification of Mathews stability graph is proposed, and a monitoring scheme combing stress, displacement, and surface subsidence is selected per the field geological condition. The displacement monitoring data and numerical model are combined, and the numerical model is corrected per the monitoring data; the time-dependent deformation and damage to the goaf is obtained; and its stability is comprehensively evaluated. Results show that the northern area is in a relatively stable stage, whilst the southern area has a certain risk of collapse. At last, the proposed framework was successfully used in the open-pit iron mine to evaluate the stability of the shallow goaf and can be used for reference to similar geological conditions.